2006
DOI: 10.1016/j.cell.2006.09.045
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of DDB1 in Mouse Brain and Lens Leads to p53-Dependent Elimination of Proliferating Cells

Abstract: DDB1, a component of the Cul4 ubiquitin ligase complex, promotes protein ubiquitination in diverse cellular functions, including nuclear excision repair, regulation of the cell cycle, and DNA replication. To investigate its physiological significance, we generated mice with null and floxed alleles of the DDB1 gene. Here we report that null mutation of DDB1 caused early embryonic lethality, while conditional inactivation of the gene in brain and lens led to neuronal and lens degeneration, brain hemorrhages, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
167
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 138 publications
(185 citation statements)
references
References 35 publications
17
167
1
Order By: Relevance
“…Although highly differentiated, hepatocytes can reenter cell cycle and self-renew in response to loss of liver mass. To analyze the role of DDB1 in hepatocyte proliferation, we generated DDB1 F/F ;Mx1-Cre +/− mice, which harbor homozygous floxed DDB1 alleles (DDB1 F ) (21) and an Mx1-Cre transgene (23). We confirmed a very efficient deletion of DDB1 in DDB1 F/F ;Mx1-Cre +/− mouse liver after one i.p.…”
Section: Ddb1mentioning
confidence: 63%
See 3 more Smart Citations
“…Although highly differentiated, hepatocytes can reenter cell cycle and self-renew in response to loss of liver mass. To analyze the role of DDB1 in hepatocyte proliferation, we generated DDB1 F/F ;Mx1-Cre +/− mice, which harbor homozygous floxed DDB1 alleles (DDB1 F ) (21) and an Mx1-Cre transgene (23). We confirmed a very efficient deletion of DDB1 in DDB1 F/F ;Mx1-Cre +/− mouse liver after one i.p.…”
Section: Ddb1mentioning
confidence: 63%
“…We previously reported that DDB1 is essential for survival of proliferating cells in mouse brain and skin, but dispensable for nondividing cells such as neurons (21,22). Although highly differentiated, hepatocytes can reenter cell cycle and self-renew in response to loss of liver mass.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the ablation of DDB1, we used DDB1 flox/flox mouse epithelial fibroblasts in which the floxed DDB1 was acutely deleted by infection of adenoviral-Cre adenovirus (58). In uninfected cells, low UVC doses of 2.2 and 4.4 J/m 2 were sufficient to lead to degradation of p12, which was significantly blocked in the Ade-Cre-infected DDB1 flox/flox mouse epithelial fibroblasts (Fig.…”
Section: Cdt2mentioning
confidence: 99%